If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 3) + 7x = 3 Reorder the terms: -5(3 + x) + 7x = 3 (3 * -5 + x * -5) + 7x = 3 (-15 + -5x) + 7x = 3 Combine like terms: -5x + 7x = 2x -15 + 2x = 3 Solving -15 + 2x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 2x = 3 + 15 Combine like terms: -15 + 15 = 0 0 + 2x = 3 + 15 2x = 3 + 15 Combine like terms: 3 + 15 = 18 2x = 18 Divide each side by '2'. x = 9 Simplifying x = 9
| -6x+9=4x-3 | | 4(x+4)+4=4x+9 | | .5x+87.5=13.25 | | 8-8x=65-29x | | x^2-6x-12= | | 35+1680x=300440 | | x/5=x/13-24 | | 550x+175=35000+1680x | | 9x^2-2x+16=0 | | n-2=19 | | n+27=48 | | (8+7x)+(20+3x)=11 | | (8+7x)+(20+3x)=180 | | 5(w+5)=-5w-15 | | 3(x-4)-4(x-3)=x+9-(x-2) | | 217-5x=31x+21 | | n-8=8 | | 5u-16=-7(u+4) | | 5x-(4-3x)=52 | | 6(x+2)=4x+22 | | (12+x)+(6x+2)=180 | | 2x+28=9-42 | | v-3/4=31/2 | | 7x-(9x+3)=4x-21 | | -2=-10 | | .6(n+10)=3.6 | | 32= | | (83-x)+(5x+11)=109 | | 1/y=y/9 | | F(x)=4x^2-17x-15 | | -2/5x=8 | | -3-6=13-10x |